Determination of a diagrammatical severity scale for net blotch in malting barley (Hordeum vulgare L.) - Petta, A. (2022)
Introduction. At present, the net blotch caused by Dreschlera teres in barley, does not have a visual scale to assess the severity of the disease in the field, therefore, the lack of a standard method for visual quantification of the disease can lead to imprecise estimates that induce to wrong conclusions. Objective. To develop a scale to assess the severity of net blotch in barley leaves. Materials and methods. One hundred leaves of different malting barley cultivars used in a trial at the experimental field of the Universidad Nacional del Noroeste de la Provincia de Buenos Aires, in the locality of Junin, Buenos Aires, Argentina, were collected in 2017, which presented different severity levels. The scale was determined with the following severity values: 1 %, 2.1 %, 4.5 %, 9.1 %, 17.8 %, 31.7 %, and 50 %. The validation of the proposed scale was carried out based on fifty barley leaves with different levels of net blotch severity, distributed to twenty evaluators without experience in estimating the damage from this disease. Validation was carried out by evaluating the severity of the leaves first without scale and then with the proposed scale. Statistical analyzes were performed using a t-test and simple linear regression. Results. The use of the scale improved the assessment of the severity in leaves with net blotch, because on average the slope of the regression of most of the evaluators increased by 15 % when they used the visual scale to evaluate the disease. Conclusion. The development of a scale to assess the severity of the net blotch in barley leaves was achieved.